HR flexibility: Precursors and the contingent impact on firm financial performance - Way, Sean A.; Wright, Patrick M.; Tracey, J. Bruce; Isnard, Jeremy F. (Human Resource Management, 2018)
Using data from 170 for‐profit U.S. firms with 100 or more employees from 27 North American Industry Classification System (NAICS) industry subsectors, we investigated firm‐level precursors of HR flexibility and industry‐level boundary conditions of the HR flexibility—firm financial performance relationship. The findings denote that a contingency illumination is warranted in which consideration should be given to firm‐level factors such as flexibility business strategy and high‐performance work systems, which may play a key role in engendering HR flexibility, and external factors such as industry dynamism and growth, which may serve as boundary conditions that influence the relevance and impact of HR flexibility. This study is an important extension of extant HR flexibility research and adds clarity regarding the roles and relevance of HR flexibility and the circumstances in which HR flexibility and/or its focal factors may augment (or diminish) firm competitiveness and performance.